2014
DOI: 10.2478/revecp-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills and Their Wage Returns: Overview of Empirical Literature

Abstract: Psychological traits, attitudes and soft skills represent factors whose effect on an individual’s wages has begun to be examined recently. Today, there is an extensive empirical body on wage returns to the first two factors, but still a relatively small one on wage returns to soft skills, such as communication, cooperation, leadership etc. The aim of this paper is to provide an overview of empirical literature on wage returns to soft skills. It suggests that soft skills are connected with significant wage retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 15 publications
1
42
0
17
Order By: Relevance
“…To remove the typos as well as recurrent superfluous adjectives 6 , results were cleaned using a script. The script removed additionally extra whitespace and punctuation, and it corrected simple typos and misspellings by comparing the detected skill tokens to a whitelist of valid skill tokens.…”
Section: Soft Skill Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove the typos as well as recurrent superfluous adjectives 6 , results were cleaned using a script. The script removed additionally extra whitespace and punctuation, and it corrected simple typos and misspellings by comparing the detected skill tokens to a whitelist of valid skill tokens.…”
Section: Soft Skill Collectionmentioning
confidence: 99%
“…where W c (s) denotes the workers who classified an occurrence of skill s to refer to a candidate, W (s) denotes the workers who assessed an occurrence of skill s, and T (w) is the trust of a worker w. Trust is calculated by the 6 The list of superfluous adjectives includes: excellent, highly, very good, good, strong, and high. crowdsourcing platform as the contributor's accuracy level in the current job, determined by his/her accuracy during the training phase -as explained in Section 2.2.1.…”
Section: Removing Ambiguous Soft Skillsmentioning
confidence: 99%
“…A interação humana requer uma capacidade que os psicólogos chamam de "teoria da mente" -a habilidade de atribuir e representar, em si próprio e nos outros, os estados mentais independentes (crenças, intenções, desejos, conhecimento, etc) e de compreender que os outros possuem crenças, desejos e intenções que são distintas da sua própria, ou mais coloquialmente "colocar-se no lugar do outro" 6 (BARON- COHEN, 2000;PREMACK;WOODRUFF, 1978;CAMERER;LOEWENSTEIN;PRELEC, 2005). À medida em que surgem evidências internacionais de que o mercado de trabalho tem valorizado essas competências (WEINBERGER, 2014;BALCAR, 2014;DEMING, 2015), é oportuno questionar a validade dessas evidências para o mercado de trabalho brasileiro. Tendo em vista que são relativamente escassos os estudos que se propõem a analisar o papel das competências socioemocionais no mercado de trabalho brasileiro, bem como o amplo reconhecimento da necessidade de investigações mais detalhadas sobre o tema, o presente estudo tem o objetivo de trazer evidências do retorno associado à essas competências usando dados nacionais.…”
Section: Lista De Ilustraçõesunclassified
“…Finally, researchers studying the relationships between skills (using the IO definition) and fields of study have found postsecondary education fosters development of general and occupation-specific skills and the amount and type of skill development varies by program and field of study (Kraebber & Greenan, 2012;Robst, 2007a). Additionally, higher levels of soft skills (e.g., cooperation, leadership) 1 , cognitive skills (e.g., critical thinking, reading comprehension), and linguistic skills are associated with significantly higher wage returns (often after controlling for participant cognitive ability; Bacolod, 2016;Balcar, 2014;Barone & van de Werfhorst, 2011). Together, this literature suggests that abilities can help individuals attain higher levels of education and make more money; meanwhile skills are acquired through postsecondary education, can be field specific, and successful mastery can contribute to higher earnings.…”
Section: Skills and Abilitiesmentioning
confidence: 99%
“…Balcar (2014) defines these as "intangible skills which are hard to measure and are closely connected with[individual's] attributes" and contrasts them to hard skills, which are "skills which re easily observable and/or measured, easily trained and closely connected with[individual's] knowledge (e.g., surgical skills or typing skills; p. 4).…”
mentioning
confidence: 99%